Toward a “Science of the Subjective”: Reminiscences and Speculations in Memory and in Honor of Bob Jahn - Bauer, Henry (Journal of Scientific Exploration, 2018)
To accommodate, explain, understand the range of phenomena often described as parapsychological or as anomalous human-machine interactions, Jahn and Dunne discussed the characteristics needed to establish a “science of the subjective”, capable of dealing with both subjective and objective information as well as transfer of information. It is suggested that work in history, or practices in the legal system, rather than the physical sciences, might offer a suitable role model; together with the substitution of Bayesian approaches for the commonly used frequentist methods of statistical analysis. Keywords: science of the subjective — Bayesian statistical analysis